Evaluation of speech signal features extraction methods - Shayeb, Ismail; Asad, Naseem; Alqadi, Ziad; Jaber, Qazem (Journal of Applied Science, Engineering, Technology, and Education, 2020)
Human speech digital signals are famous and important digital types, they are used in many vital applications which require a high speed processing, so creating a speech signal features is a needed issue. In this research paper we will study more widely used methods of features extraction, we will implement them, and the obtained experimental results will be compared, efficiency parameters such as extraction time and throughput will be obtained and a speedup of each method will be calculated. Speech signal histogram will be used to improve some methods efficiency.